2022
DOI: 10.1186/s40359-022-00917-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of mental health problems among stranded international students during the COVID-19 pandemic

Abstract: Background The novel coronavirus disease (COVID-19) spread fast throughout China and the rest of the world, prompting the World Health Organization to declare a worldwide pandemic on March 11, 2020. Many countries have implemented travel bans, lockdowns, and stay-at-home policies to combat the spread of the COVID-19 pandemic. This study aimed to investigate the risk factors of mental health problems among international students stranded outside of China during the pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Notably, the prevalence of mental health problems, including anxiety and depression, among this demographic has been a significant concern. Studies such as those by Iftikhar et al ( 8 ) and Kim and Choi ( 42 ) shed light on the prevalence of mental health problems, highlighting the need for targeted interventions. Additionally, factors exacerbating mental health issues among international students have been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the prevalence of mental health problems, including anxiety and depression, among this demographic has been a significant concern. Studies such as those by Iftikhar et al ( 8 ) and Kim and Choi ( 42 ) shed light on the prevalence of mental health problems, highlighting the need for targeted interventions. Additionally, factors exacerbating mental health issues among international students have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Critical Mental Health Status of the International Students – The comprehensive review of the literature on the mental health of international students since the beginning of the COVID-9 pandemic, when the current project was started, was corroborated by an important number of emerging studies that put efforts to provide scientific evidence of their critical status. As summarized, various aspects of the mental health of international students during the COVID-19 pandemic have been reported worldwide ( 8 , 9 , 53 ) (more recorded in Tables 1B,C ).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that negative effects of the COVID-19 pandemic were present in both groups of students, but in different ways: while domestic students had their mental health and social and emotional aspects worsened during the COVID-19 pandemic, international students presented a poorer mental health status overall. It indicates that mental health care should address both groups, with special attention on international students, taking into consideration the specificities they may present [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about visa status and consequent disruption of studies were reported by international students in the US [42]. A qualitative study conducted in China indicated hopelessness, uncertainty, worry, lack of interest and focus, lack of support, financial difficulties, social pressure, sleep disorders, and increased smoking among international students [28]. Therefore, visa and financial issues, language skills, acculturation problems, poor social support systems, cultural and social adjustment, academic adaptation, homesickness, and lack of knowledge about the healthcare system are some examples of the challenges faced by international students in particular [17,[43][44][45][46].…”
Section: Plos Onementioning
confidence: 99%
“…People who experience mental illness can experience a range of issues, including low mood (Ibrahim et al , 2020), difficulties with concentration (Iftikhar et al , 2022), impaired functioning (Lambert et al , 2020) and suicidal ideation (Saab et al , 2022). Once people engage with mental health services and access appropriate treatments, they can often see improvements in their overall mental health (Puffer et al , 2020; Malins et al , 2021) and are more likely to be provided with the education, resources and support they need to help maintain their well-being and reduce the risk of relapse (Coiro et al , 2017; Nolan and Petrakis, 2019).…”
Section: Introductionmentioning
confidence: 99%